The E2A-HLF Oncoprotein Activates Groucho-Related Genes and Suppresses Runx1 - Dang, Jinjun (American Society for Microbiology, 2001)
The E2A-HLF fusion gene, formed by the t(17;19)(q22;p13) chromosomal translocation in leukemic pro-B cells, encodes a chimeric transcription factor consisting of the transactivation domain of E2A linked to the bZIP DNA-binding and protein dimerization domain of hepatic leukemia factor (HLF). This oncoprotein blocks apoptosis induced by growth factor deprivation or irradiation, but the mechanism for this effect remains unclear. We therefore performed representational difference analysis (RDA) to identify downstream genetic targets of E2A-HLF, using a murine FL5.12 pro-B cell line that had been stably transfected with E2A-HLF cDNA under the control of a zinc-regulated metallothionein promoter. Two RDA clones, designated RDA1 and RDA3, were differentially upregulated in E2A-HLF-positive cells after zinc induction. The corresponding cDNAs encoded two WD40 repeat-containing proteins, Grg2 and Grg6. Both are related to the Drosophila protein Groucho, a transcriptional corepressor that lacks DNA-binding activity on its own but can act in concert with other proteins to regulate embryologic development of the fly. Expression of both Grg2 and Grg6 was upregulated 10- to 50-fold by E2A-HLF. Immunoblot analysis detected increased amounts of two additional Groucho-related proteins, Grg1 and Grg4, in cells expressing E2A-HLF. A mutant E2A-HLF protein with a disabled DNA-binding region also mediated pro-B cell survival and activated Groucho-related genes. Among the transcription factors known to interact with Groucho-related protein, only RUNX1 was appreciably downregulated by E2A-HLF. Our results identify a highly conserved family of transcriptional corepressors that are activated by E2A-HLF, and they suggest that downregulation of RUNX1 may contribute to E2A-HLF-mediated leukemogenesis.